Dinamika Konflik dalam Organisasi: Identifikasi Ciri-Ciri dan Faktor Penyebabnya - I Gusti Ayu Apsari Pradnya Dewi; Ni Putu Keisya Anatasia; Ni Kadek Dwi Anatasya; Ni Putu Friska Ayu Damayanti; Ni Luh Nadia Eka Yanthi (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine in depth the concept of conflict, characteristics of conflict, and factors causing conflict based on theoretical perspectives and previous research findings. This study uses a qualitative approach with a library research method, which utilizes secondary data in the form of textbooks on management and organizational behavior, national and international scientific journals, and academic articles relevant to the topic of conflict. Data collection was conducted through documentation studies, then analyzed using qualitative descriptive analysis techniques by classifying conflict concepts, identifying the main characteristics of conflict, and analyzing various factors causing conflict in a systematic and comprehensive manner. The results of the study show that conflict is a phenomenon that cannot be separated from the dynamics of individual and group interactions in organizations and educational environments. Conflict generally arises due to differences in interests, perceptions, values, attitudes, backgrounds, and goals to be achieved. Therefore, a comprehensive understanding of the concepts, characteristics, and causes of conflict is very important as a basis for designing effective, constructive, and sustainable conflict management strategies to improve organizational performance and the quality of work and learning relationships.